Correlation between microstructure and drastically reduced lattice thermal conductivity in bismuth telluride/bismuth nanocomposites for high thermoelectric figure of merit. (December 2015) - Misra, D.K.; Sumithra, S.; Chauhan, N.S.; Nolting, W.M.; Poudeu, P.F.P.; Stokes, Kevin L.
Abstract: The concept of nanocomposite/nanostructuring in thermoelectric materials has been proven to be an effective paradigm for optimizing the high thermoelectric performance primarily by reducing the thermal conductivity. In this work, we have studied the microstructure details of nanocomposites derived by incorporating a semi-metallic Bi nanoparticle phase in Bi2 Te3 matrix and its correlation mainly with the reduction in the lattice thermal conductivity. Incorporating Bi inclusion in Bi2 Te3 bulk thermoelectric material results in a substantial increase in the power factor and simultaneous reduction in the thermal conductivity. The main focus of this work is the correlation of the microstructure of the composite with the reduction in thermal conductivity. Thermal conductivity of the matrix and nanocomposites was derived from the thermal diffusivity measurements performed from room temperature to 150 °C. Interestingly, significant reduction in total thermal conductivity of the nanocomposite was achieved as compared to that of the matrix. A detailed analysis of high-resolution transmission electron microscope images reveals that this reduction in the thermal conductivity can be ascribed to the enhanced phonon scattering by distinct microstructure features such as interfaces, grain boundaries, edge dislocations with dipoles, and strain field domains.